On wage policies and unemployment - Andreas Irmen (The Open Economics Journal, 2009)
In economies where the price of labour is determined outside of competitive markets the question arises as to whether the observed evolution of wages is likely to contribute to a decline in unemployment. I develop and discuss a benchmark, the neutral wage policy, to which the actual evolution of wages can be compared. Here, neutrality refers to the unemployment rate and not to the level of employment. If the actual wage growth falls short of this benchmark then the evolution of wages is said to have contributed to a decline in the unemployment rate. This benchmark is based on fairly general assumptions on the aggregate production technology, incorporates changes in the supply of labour, and accounts for changes in the competitive environment of firms. Finally, I discuss the relation to the benchmark of the German Council of Economic Experts [1].
Keywords: 330; productivity growth; wages; employment